2020
DOI: 10.1186/s12014-020-09272-z
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ultraviolet- and infrared-based laser microdissection technology on phosphoprotein detection in the laser microdissection-reverse phase protein array workflow

Abstract: Reversible protein phosphorylation represents a key mechanism by which signals are transduced in eukaryotic cells. Dysregulated phosphorylation is also a hallmark of carcinogenesis and represents key drug targets in the precision medicine space. Thus, methods that preserve phosphoprotein integrity in the context of clinical tissue analyses are crucially important in cancer research. Here we investigated the impact of UV laser microdissection (UV LMD) and IR laser capture microdissection (IR LCM) on phosphoprot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Previous proteomic studies relied on whole tissue lysates derived from samples with uncontrolled cellular input including mixtures of stroma, immune cell and tumor epithelium, fat, fibroblasts, etc., and did not adequately enrich for any cell type greater than 90%, which we have demonstrated greatly impacts the accuracy of protein and protein signaling data. 25 , 26 , 27 , 28 , 29 A further distinctive aspect of our analysis is that the protein expression and signaling activation data were derived from treatment-naive breast cancer tumor cells and that the study was undertaken to identify actionable protein targets that could be used to prioritize treatment strategies for future studies and in non-responding patient cohorts. These data and transcriptional profiling 6 —the I-SPY2-990 Data Resource compendium—are now publicly available to the research community.…”
Section: Discussionmentioning
confidence: 99%
“…Previous proteomic studies relied on whole tissue lysates derived from samples with uncontrolled cellular input including mixtures of stroma, immune cell and tumor epithelium, fat, fibroblasts, etc., and did not adequately enrich for any cell type greater than 90%, which we have demonstrated greatly impacts the accuracy of protein and protein signaling data. 25 , 26 , 27 , 28 , 29 A further distinctive aspect of our analysis is that the protein expression and signaling activation data were derived from treatment-naive breast cancer tumor cells and that the study was undertaken to identify actionable protein targets that could be used to prioritize treatment strategies for future studies and in non-responding patient cohorts. These data and transcriptional profiling 6 —the I-SPY2-990 Data Resource compendium—are now publicly available to the research community.…”
Section: Discussionmentioning
confidence: 99%
“…We cannot exclude the possibility that the lack of concordance between DNA alterations and RNA and protein and protein phosphorylation are not merely the result of tumor heterogeneity and the tumor cellularity of the samples. Previous studies have investigated the impact of laser capture dissection as an approach for tumor cell enrichment, and found that laser capture microdissection (LCM) has no detrimental effect on RPPA data, but rather increases accuracy and quality of RPPA data (56,57). In another study, tumor cell enrichment using LCM resulted in the identification of molecular associations, such as PTEN protein expression, was reduced only in dissected samples with PTEN alterations, which was missed when whole tissue lysates were used (58).…”
Section: Discussionmentioning
confidence: 99%
“…Microdissected caps were stored at −80°C until further processed. We have previously demonstrated that this procedure does not affect protein integrity and post-translational modifications providing an excellent enrichment method for downstream analysis of human specimens ( Baldelli et al., 2015 ; Hunt et al., 2020 ).…”
Section: Methodsmentioning
confidence: 99%